Neuraxial blocks in parturients with scoliosis and after spinal surgery - Mouveen Sharma; Ian McConachie (Wolters Kluwer Medknow Publications, 2016)
Neuraxial blocks in parturients with scoliosis and/or previous back surgery have traditionally been avoided due to concerns such as difficulty, increased complications, and decreased efficacy. Recent studies suggest that with attention to proper anesthetic technique and improvements in surgical procedures the success rate of neuraxial blocks is improved. The use of ultrasound may also improve the success rate of neuraxial blocks and should be considered. We review the recent literature and suggest practical approaches to neuraxial blocks in these parturients.